(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2021)
The main goal of this study lies in revealing the social and cultural significance of Oswaldo Guayasamín for Ecuador, he was an emblematic figure in the field of Plastic Arts in that country. From a methodological point of view, the current study is a qualitative research with a hermeneutic approach. It is an empirical documentary study centered on primary sources. The design corresponds to the descriptive transactional nonexperimental research. To achieve the objective, a reference corpus of two works by the Ecuadorian artist was used; they were analyzed with Iuri Lotman Theory support, using the cultural semiotic method, as well as the exegetic technique that allows valuing hermeneutically the selected pictorial corpus. So, the objective of this discussion is to analyze four works of the author, with support of Iuri Lotman’s theory, using the author’s cultural semiotic method, as well as the exegetic technique that allows to hermeneutically assess the selected pictorial corpus. The main findings include: Guayasamín’s paintings express a vision that defends the rights of the indigenous race, especially women and children. These paintings date back to the twentieth century when unfair treatment and contempt, abuse, violence, and exploitation of mestizo cultures, indigenous and black, were evident at a time full of world wars, civil wars, and exploitation. The application of the theoretical aspects of Iuri Lotman revealed that Guayasamín’s paintings are a demonstration of his time background reality and show indigenous people’s feelings of suffering, anger, and frustration in a particular historical context..